Investigating the joint effects of overload and underload on chronic fatigue and wellbeing - Cham, Belinda; Andrei, Daniela; Griffin, Mark; Grech, M.; Neal, A. (2021)
Workers in safety critical and 24-hour operating environments face sustained exposure to many stressful situations, ranging from long periods of monotony and boredom, to sudden periods of intense time pressure. This study examines how the combination of overload and underload contributes to fatigue and wellbeing in 943 seafarers. Using latent moderated structural equation modelling, we found that underload showed a stronger association with chronic fatigue and impaired wellbeing, compared to overload. An interaction between overload and underload was also significantly related to psychological wellbeing, with increasing levels of overload weakening the negative relationship between underload and psychological wellbeing. Our research highlights that underload, despite previously not receiving much attention, is an important area of concern. Our findings also underscore the importance of unpacking the joint effects of concurrent job demands, and to consider how certain job demands may help to reduce the negative effects caused by other demands. Where current and future jobs may be subject to a reduction in demands (e.g. automation), it is important to consider how underload may impact worker fatigue and wellbeing.